Irum ki uran - Jawad, Ahmed Rasheed (Feroz sons Karachi, 1999)
"Irum ki Udaan" is a story about a girl named Irum who dreams of flying. She builds a special parachute and takes a daring leap, soaring through the sky. This story celebrates courage, imagination, and the thrill of adventure.